THE ROLE OF CORPORATE CULTURE IN THE FORMATION OF A NEW STRATEGY AND BUSINESS MODEL OF HOSPITALITY ENTERPRISES - KAPLINA, Tatyana; KAPLINA, Anna; KUSHCH, Larisa; DUDNYK, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to summarize approaches of corporate culture and define its role as a strategic competitive advantage of the hospitality industry. The solution of the tasks set in the article is carried out with the help of the following general and special research methods: analysis, synthesis, systematization and generalization. According to the results of theoretical research, the concept of «corporate culture» is defined. The question of the influence of corporate culture on the competitiveness of the hotel enterprise is investigated. The realization of directions of corporate culture is considered on the example of the operating hotel. Guest feedback was analyzed, a profile program was built according to the main descriptors. Approaches to the essence of the concept of corporate culture and definition of its role as a strategic competitive advantage of the enterprise are generalized. The role of corporate culture in the field of hospitality is determined. Attention to optimizing the elements of corporate culture of the hotel enterprise is paid. The introduction of corporate culture standards in the management of the hospitality industry is established and it can become an element in the strategic management model in a chaotic environment that will protect the company from an increasingly unpredictable environment, especially in times of crisis. It is determined that the introduction of various strategic models of corporate culture will improve the organizational culture of the enterprise, creating additional benefits of the competitiveness of the enterprise in the service sector, highlighting it in a particularly attractive brand. The development of corporate culture is proved as the contributor to the success of the hospitality industry as it helps the hotel and restaurant industry to become competitive and efficient in the services market.
Keywords: corporate culture; hospitality industry; enterprise competitiveness; personnel; manager; values; role of corporate culture